Awareness about Antenatal Care Services among Rural Pregnant Women (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Antenatal care (ANC) is the care of a pregnant woman required to ensure a healthy pregnancy and safe childbirth. According to the World Health Organization to achieve the full life-saving potential for pregnant women and babies, minimum four ANC visits are essential. Quality and quantity of ANC visit depends on socio-demographic characteristics, knowledge, awareness and attitude of the individual. To get the benefits from ANC services awareness among pregnant women and their family members are very important.Objective: To evaluate the awareness about ANC service among the pregnant women attending Upazila Health Complex of a rural community.Materials and Methods: This descriptive cross-sectional study was conducted among the pregnant women attending the outpatient department of Kaligonj Upazila Health Complex, Gazipur, Bangladesh from January to March 2017. Data were collected by face-to-face interview of the respondents using a structured questionnaire. Chi-square (χ2) test was done to see the association among the respondents’ socio-demographic characteristics with awareness about ANC services.Result: Respondents’ age range was 16-40 years and 61.9% were below 25 years and 71.1% married before 20 years. More than half (66.5%) of the respondents’ found aware about pregnancy danger sign, safe delivery and benefits of ANC service. This study found a significant (p